2010
DOI: 10.1063/1.3508954
|View full text |Cite
|
Sign up to set email alerts
|

Low resistance, high dynamic range reconfigurable phase change switch for radio frequency applications

Abstract: A GeTe reconfigurable phase change switch for radio frequency applications is presented. Low ON state resistance (180 Ω) and large dynamic range (7×103 X) were achieved through low resistance electrode design and high current. A partial crystallization and partial reamorphization model is proposed to explain the differences between the measured and calculated device ON (set) and OFF (reset) state resistances, respectively. The dependency between ON state resistance and reset current was estimated using a first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 8 publications
0
24
0
1
Order By: Relevance
“…We investigate the corresponding RF S-parameter properties up to 13.5 GHz and power handling capabilities for possible RF applications in high frequency filters, modulators, and active microwave device components. 3,5,[10][11][12][13][14][15][16] We show that high RF input power can reduce the resistance of VO 2 similarly as applied DC voltage. We compare transient and RF properties with published results on VO 2 and present lumped circuit element and 3D electromagnetic simulations that model the RF properties quite well.…”
Section: Introductionmentioning
confidence: 99%
“…We investigate the corresponding RF S-parameter properties up to 13.5 GHz and power handling capabilities for possible RF applications in high frequency filters, modulators, and active microwave device components. 3,5,[10][11][12][13][14][15][16] We show that high RF input power can reduce the resistance of VO 2 similarly as applied DC voltage. We compare transient and RF properties with published results on VO 2 and present lumped circuit element and 3D electromagnetic simulations that model the RF properties quite well.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the reverse phase transition experiments failed due to instrument limitations, e.g., interference from voltage source meter (resulting undesired phase change) and inability to achieve fast enough quenching rate. Wen et al suggested using a voltmeter in conjunction with a separate current source meter to resolve the first issue [17]. Therefore, it is with certain modifications in our experimental setup that we will be able to demonstrate crystalline to an amorphous phase transition.…”
Section: Discussionmentioning
confidence: 99%
“…Thin film GeTe is very attractive as an RF switch because its crystalline (on-state) resistivity is amongst the lowest known for a phase change material, our films measuring at 3.1 Â 10 À4 X-cm at room temperature; thin film crystalline GeTe has been reported as low as 1.6 Â 10 À4 X-cm, 8 approaching bulk GeTe's 1.1-1.5 Â 10 À4 X-cm. 9,10 The amorphous to crystalline transformation occurs at a relatively high $190 C. 11,12 The most studied phase change material is the Ge-Sb-Te system, with the alloy Ge 2 Sb 2 Te 5 (GST) being extensively used in the optical storage industry due to its high speed of transition and large swing in reflectivity between crystalline and amorphous states. GST has also been applied to resistance memory; a resistive memory based on Ge-Sb-Te has demonstrated reliable voltage switching to more than 1 Â 10 12 cycles.…”
mentioning
confidence: 99%
“…GST has also been applied to resistance memory; a resistive memory based on Ge-Sb-Te has demonstrated reliable voltage switching to more than 1 Â 10 12 cycles. 13 Previous researchers have built RF switches using phase change materials, based on the vertical memory cell 11,14,15 which have shown progressively better RF performance with Shim et al 15 demonstrating an insertion loss < 1 dB in a SPST (single-pole single-throw) configuration. To achieve a low RF loss, several vias must be placed in parallel to bring the switch resistance below 1 X.…”
mentioning
confidence: 99%
See 1 more Smart Citation